Die vryheid van die teologie in die nuwere RoomsKatolieke denke - Wethmar, C. J. (Verbum et ecclesia, 1995)
The freedom of theology according to recent Roman Catholic thought In this article the notion of the freedom of theology in recent Roman Catholic thought is discussed with special reference to the Vatican Instruction "Donum Veritatis", which outlines the current views in this church on the ecclesial vocation of the theologian. The factors which prompted the publication of this document are described as well as the tradition within which it is situated. A careful analysis of the structure and contents of the Instruction is made and the basic presuppositions of its notion of theology are indicated. The article concludes with a Refonned response to the central argument of the document.